Measles: A disease that’s making a comeback - Bojarska, Małgorzata; Domańska, Natalia; Brzyska, Anna; Bogucka, Julia; Wilczek, Natalia; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Introduction: Measles is a highly contagious viral disease that occurs around the world, featured by fever and the characteristic maculopapular rash, which can also be associated with cough, conjunctivitis or coryza. In recent years, there has been an alarming increase in the amount of measles cases in many countries around the world. The aim of this study is to review the literature and systematize knowledge about measles. Brief description of the state of knowledge: The disease is caused by the measles virus, which is highly infectious, and its only reservoir is humans. The infection occurs via droplets, and the disease is a three-phase course. Unfortunately, measles is behind multiple complications, which may lead to death. In view of no specific antiviral therapies available for the treatment of measles, controlling the spread of the disease depends on prophylaxis, that is the use of widely available and effective vaccination against measles. Despite the presence of vaccines, there is still a substantial risk of further endemic outbreaks. Conclusions: Nowadays, the elimination of measles is a major challenge due to increasing population density, ongoing wars, pandemics and other social and political factors. Hence, it remains paramount to make every effort to increase the quantity of people vaccinated against measles and to control its spread globally.